HUBUNGAN STATUS SOSIAL EKONOMI DAN KOMITMEN LINGKUNGAN HIDUP IBU-IBU PKK TERHADAP BUDAYA BERSIH DI KELURAHAN KLENDER KECAMATAN DUREN SAWIT JAKARTA TIMUR HERAWATI ABSTRACT - Herawati Herawati (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2016)
The objective of this research is to analyze the relationship of social economic status and environmental commitment the mothers in PKK the area in klender Jakarta east. The sample of this research were 76 persons which randomly taken. The data were analyzed by using ANAVA 2 X 2. Findings of the research indicated that the mother PKK doers who were relationship of social economic status and environmental commitment the mothers in PKK the area in klender Jakarta east. Therefore, the two variables should be taken into consideration to increase the Doers’enviromental commitment on mothers PKK in klender Jakarta east.